Application of Balanced Scorecard to Enhance Company Performance: An Economic Perspective - Ayyasy, Ahmad Nafis; Winanti, Winanti; Shintya Maelani (Yayasan Riset dan Pengembangan Intelektual, 2025)
This article examines the application of the Balanced Scorecard (BSC) as a tool for improving company performance. The BSC framework evaluates performance from four key perspectives: financial, customer, internal business processes, and learning and growth. By incorporating both short-term results and long-term strategic goals, BSC offers a holistic approach to management. The study explores how the implementation of BSC can help organizations achieve their strategic objectives, enhance operational efficiency, and improve both customer and employee satisfaction. Case studies from companies that have adopted BSC demonstrate its effectiveness in improving performance oversight, fostering innovation, and driving long-term organizational growth. These insights contribute to a deeper understanding of how BSC can be used to enhance competitiveness and achieve sustainable business success.